Analysis of strategic directions in sustainable hydrogen investment decisions - Zhu, Lu; Hu, Lanli; Yüksel, Serhat; Dinçer, Hasan; Karakuş, Hüsne; Ubay, Gözde Gülseven (MDPI, 2020)
This study seeks to find the appropriate strategies necessary to make sustainable and effective hydrogen energy investments. Within this scope, nine different criteria are defined regarding social, managerial, and financial factors. A hesitant, interval-valued, intuitionistic fuzzy (IVIF) decision-making trial and evaluation laboratory (DEMATEL) methodology is considered to calculate the degree of importance of the criteria. Additionally, impact relation maps are also generated to visualize the causality relationship between the factors. The findings indicate that the technical dimension has the greatest importance in comparison to managerial and financial factors. Furthermore, it is also concluded that storage and logistics, research and development, and technological infrastructure are the most significant factors to be considered when defining hydrogen energy investment strategies. Hence, before investing in hydrogen energy, necessary actions should be taken to minimize the storage and logistic costs. Among them, building the production site close to the usage area will contribute significantly to this purpose. In this way, possible losses during the transportation of hydrogen can be minimized. Moreover, it is essential to identify the lowest-cost hydrogen storage method by carrying out the necessary research and development activities, thereby increasing the sustainability and effectiveness of hydrogen energy investment projects.
Keywords: Sustainability; Energy Production; Hydrogen Energy; Hesitant IVIF DEMATEL